Inherent Mothering Ability of Indigenous Hen under Extensive Free-Range Management, A-Close Observational Study - Nyandebo, Jesse Patrick Joseph; Bagla, Victor Patrick; Kanu, Saidu; Muana, Abigail; Sesay, Abdul Rahman; Umoh, Magdalene Philips (International Journal of Scientific Research and Management (IJSRM), 2022)
Inherent mothering ability of the indigenous hen under extensive management is geared towards ensuring continuation of its lineage. Most of these attributes (feeding and predators response) are instinctive and transmitted to chicks during their first week of life to enhance their survival.The study was carried out over a ten-years period base on direct keen observation of the indigenous hen from the point of attainment of puberty and associating with cocks up to the time it’s raising her own brood under extensive management and recordings of inherent and instinctive traits exhibited. Maternal behaviours like egg incubation; candling and sorting; egg turning; temperature regulation and hatching are in synchrony with the hatching machine. Chick brooding and rearing periods presents the most challenging time as she has to balance between two key responsibilities (feeding and chick protection), these it was observed she do diligently to ensure the propagation of its lineage though faced with huge challenges from predators and adverse weather conditions that reduce chick population reaching maturity.This research findings recommends feed supplementation especially during incubation, brooding and chick rearing period and confinement and protection of young chicks from predators and adverse weather conditions until they reach weaning age.